A consideration of the relative contributions of different microbial subpopulations to the soil N cycle - Bottomley, Peter; Taylor, Anne E.; Myrold, David D. (Frontiers in Microbiology, 2012)
We examine and discuss literature targeted at identifying “active” subpopulations of soil microbial communities with regard to the factors that affect the balance between mineralization and immobilization/assimilation of N. Whereas a large fraction (≥50%) of soil microbial biomass can immediately respire exogenous substrates, it remains unclear what percentage of both bacterial and fungal populations are capable of expressing their growth potential. The factors controlling the relative amounts of respiratorily responsive biomass versus growth-active biomass will impact the balance between N mineralization and N immobilization. Stable isotope probing of de novo DNA synthesis, and pyrosequence analyses of rRNA:rDNA ratios in soils have identified both numerically dominant and rare microbial taxa showing greatest growth potential. The relative growth responses of numerically dominant or rare members of a soil community could influence the amount of N immobilized into biomass during a “growth” event. Recent studies have used selective antibiotics targeted at protein synthesis to measure the relative contributions of fungi and bacteria to ammonification and NH4+ consumption, and of NH3 oxidizing archaea (AOA) and bacteria (AOB) to NH3 oxidation. Evidence was obtained for bacteria to dominate NH4+ assimilation and for fungi to be involved in both consumption of dissolved organic nitrogen (DON) and its ammonification. Soil conditions, phase of cropping system, NH4+ availability, and soil pH influence the relative contributions of AOA and AOB to soil nitrification. A recent discovery that AOA can ammonify organic N sources and oxidize it to NO2- serves to illustrate roles for AOA in both the production and consumption of NH3/NH4+. Clearly, much remains to be learned about the factors influencing the relative contributions of bacteria, archaea and fungi to processing organic and inorganic N, and their impact on the balance between mineralization and immobilization of N.